Layered positive electrode material of sodium-ion battery as well as preparation method and application of layered positive electrode material
By introducing sodium vacancy and calcium elements into the layered positive electrode material of sodium ion battery and doping transition metal elements, the problems of poor discharge capacity and cycling performance of existing materials are solved, and high discharge specific capacity and excellent cycling stability are achieved. Suitable for low-speed electric vehicles.
Patent Information
- Application Number
- CN202411370836.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
AI Technical Summary
The existing O3-type sodium ion battery layered positive electrode material has insufficient discharge capacity and poor circulation performance, which cannot meet the needs of low-speed electric vehicles.
By introducing sodium vacancies and calcium elements into the sodium layer and controlling their proportional relationship, combining the doping of Ni, Fe, Co, Mn and Ti elements, a high-temperature solid-phase sintering method is used to prepare a layered positive electrode material of sodium ion battery to regulate sodium Layer spacing and structural stability.
It improves the discharge specific capacity and cycle stability of the layered positive electrode material of sodium ion battery, and is suitable for low-speed electric vehicle applications.
Smart Images

Figure CN119133435A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a sodium ion battery layered positive electrode material and a preparation method and application thereof. Background Art
[0002] Existing O3-type sodium-ion battery layered cathode materials often have the disadvantages of insufficient discharge capacity and poor cycle performance, and therefore cannot meet the needs of future low-speed electric vehicle application scenarios. Although increasing the nickel content in the layered cathode material of the sodium-ion battery can increase the number of redox active centers during the charge and discharge process and effectively improve the discharge capacity of the layered cathode material of the sodium-ion battery, its cycle stability is still poor. Summary of the invention
[0003] Based on this, it is necessary to provide a sodium ion battery layered positive electrode material and a preparation method and application thereof to address the above problems. The sodium ion battery layered positive electrode material has a high discharge specific capacity and excellent cycle stability.
[0004] A sodium ion battery layered positive electrode material, wherein the physical phase of the sodium ion battery layered positive electrode material is an O3 phase, and the molecular formula of the sodium ion battery layered positive electrode material is [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O2, where □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1.
[0005] In one embodiment, the sodium interlayer spacing of the sodium ion battery layered positive electrode material is d O-Na-O ,
[0006] In one embodiment, taking the sum of the molar numbers of Ni, Fe, Co, Mn and Ti in the sodium ion battery layered positive electrode material as 100, in any two regions of the same area of the sodium ion battery layered positive electrode material, the standard deviation of the Ni content is less than 0.2, the standard deviation of the Fe content is less than 0.3, the standard deviation of the Co content is less than 0.3, the standard deviation of the Mn content is less than 0.3, and the standard deviation of the Ti content is less than 0.1.
[0007] In one embodiment, the particles of the sodium ion battery layered positive electrode material are plate-like particles, and the median particle size of the plate-like particles is 3 μm-5 μm.
[0008] In one embodiment, the SPAN value of the sodium ion battery layered cathode material is 1.0-3.0.
[0009] In the sodium ion battery layered positive electrode material of the present invention, by simultaneously introducing sodium vacancies and calcium elements in the sodium layer, and controlling the proportional relationship between the calcium element and the sodium vacancies, the sodium interlayer spacing in the sodium ion battery layered positive electrode material can be accurately regulated, and the sodium interlayer spacing is controlled within a suitable range, so that the sodium ion diffusion kinetics can be accelerated, more sodium ions can be reversibly deintercalated, and the discharge specific capacity can be improved while the structural stability of the sodium ion battery layered positive electrode material is improved. At the same time, the introduction of Ni, Fe, Co, Mn and Ti elements at the transition metal site can further improve the discharge specific capacity and structural stability of the sodium ion battery layered positive electrode material. Therefore, the sodium ion battery layered positive electrode material of the present invention has a high discharge specific capacity and excellent cycle stability, so that the application of sodium ion batteries in low-speed electric vehicles can be better promoted.
[0010] A method for preparing the layered positive electrode material for a sodium ion battery as described above comprises the following steps:
[0011] With [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O2 is used as a reference, wherein □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1, a sodium source, a calcium source, a nickel source, an iron source, a cobalt source, a manganese source and a titanium source are mixed to obtain a mixture, wherein the sodium source is in excess of 6%-10% based on the sodium element;
[0012] The mixture is sintered to obtain a sodium ion battery layered positive electrode material, wherein the sintering includes a first sintering and a second sintering, the first sintering temperature is 800°C-1000°C, the first sintering time is 12h-24h, the second sintering temperature is 600°C-900°C, and the second sintering time is 6h-12h.
[0013] In one embodiment, in the step of sintering the mixture, at least one of the following conditions is met:
[0014] (1) placing the mixture in an air atmosphere for sintering;
[0015] (2) The mixture is first subjected to a first sintering, and then crushed, separated and screened to obtain an intermediate; and then the intermediate is subjected to a second sintering, and then crushed, separated and screened.
[0016] In one embodiment, the median particle size of the intermediate is 3 μm-5 μm.
[0017] In the preparation method of the sodium ion battery layered positive electrode material of the present invention, a high-temperature solid phase method is adopted to control the addition ratio of each raw material and limit the specific conditions of sintering, so as to obtain sodium vacancies and calcium elements with a specific ratio relationship in the sodium layer. The operation method is simple and easy to mass produce.
[0018] A positive electrode sheet prepared using the sodium ion battery layered positive electrode material as described above.
[0019] A sodium ion battery prepared using the positive electrode sheet as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is a scanning electron microscope (SEM) image of the sodium ion battery layered positive electrode material of Example 1 of the present invention;
[0022] Figure 2 X-ray diffraction (XRD) patterns of the sodium ion battery layered positive electrode materials of Examples 1, 4 to 9 of the present invention, wherein in the figure, A represents Example 1, B represents Example 4, C represents Example 5, D represents Example 6, E represents Example 7, F represents Example 8, and G represents Example 9;
[0023] Figure 3 It is an enlarged view near the (003) peak in the X-ray diffraction (XRD) spectrum of the sodium ion battery layered positive electrode material of Example 1 and Comparative Examples 1 to 5 of the present invention, wherein, in the figure, A represents Comparative Example 2, B represents Comparative Example 5, C represents Example 1, D represents Comparative Example 1, E represents Comparative Example 4, and F represents Comparative Example 3;
[0024] Figure 4The charge and discharge curves of the sodium ion battery layered positive electrode materials of Example 1 and Comparative Examples 1 to 5 of the present invention after stable cycling in a half-cell, wherein in the figure, A represents Comparative Example 2, B represents Comparative Example 5, C represents Comparative Example 1, D represents Comparative Example 4, E represents Comparative Example 3, and F represents Example 1;
[0025] Figure 5 The charge-discharge cycle performance curves of the sodium ion battery layered positive electrode materials of Example 1 and Comparative Examples 1 to 5 of the present invention after 50 cycles under full battery, wherein, in the figure, A represents Example 1, B represents Comparative Example 1, C represents Comparative Example 2, D represents Comparative Example 3, E represents Comparative Example 4, and F represents Comparative Example 5;
[0026] Figure 6 X-ray diffraction (XRD) patterns of the sodium ion battery layered positive electrode materials of Comparative Examples 1 and 2 of the present invention in the initial state and after 10 cycles in the half-cell, wherein, in the figure, B1 represents Comparative Example 1 in the initial state, B2 represents Comparative Example 1 after 10 cycles in the half-cell, C1 represents Comparative Example 2 in the initial state, and C2 represents Comparative Example 2 after 10 cycles in the half-cell;
[0027] Figure 7 It is a relative trend chart of the discharge specific capacity and 50-cycle capacity retention rate of the sodium ion battery layered positive electrode materials of Example 1, Example 6 to Example 9 and Comparative Examples 1 to Example 5 of the present invention, wherein, in the figure, N represents the discharge specific capacity curve, and P represents the capacity retention rate curve. DETAILED DESCRIPTION
[0028] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0030] The sodium ion battery layered positive electrode material provided by the present invention has a physical phase of O3 phase and a molecular formula of [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O2, where □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1.
[0031] In the sodium ion battery layered positive electrode material of the present invention, by introducing sodium vacancies in the sodium layer, the interlayer spacing can be widened, the sodium ion diffusion kinetics can be accelerated, and more sodium ions can be reversibly deintercalated, thereby improving the discharge specific capacity. At the same time, the calcium ions and the sodium ions have similar radii, so that the calcium ions enter part of the sodium vacancies and play a supporting role in the sodium layer, which can stabilize the main structure of the sodium ion battery layered positive electrode material, inhibit interlayer slip during charging and discharging, regulate the interlayer spacing, and improve the cycle stability of the sodium ion battery layered positive electrode material. Therefore, by simultaneously introducing sodium vacancies and calcium elements in the sodium layer, under the synergistic effect of sodium vacancies and calcium elements, the cycle stability can be improved while improving the discharge specific capacity of the sodium ion battery layered positive electrode material.
[0032] Furthermore, by controlling the ratio between calcium and sodium vacancies, the sodium interlayer spacing in the layered positive electrode material of the sodium ion battery can be precisely controlled and kept within an appropriate range, which can give full play to the synergistic effect between calcium and sodium vacancies and improve the discharge specific capacity and cycle stability of the layered positive electrode material of the sodium ion battery.
[0033] In addition, according to the molecular formula of the layered positive electrode material for sodium ion batteries, it can be known that the corresponding cation parameters a, b, c, d and e at the transition metal site can be adjusted according to actual needs to control the doping amounts of Ni, Fe, Co, Mn and Ti at the transition metal site, wherein Ni can be used as the redox center of the layered positive electrode material for sodium ion batteries, and by controlling the content of Ni, 0.4≤a<0.5, the layered positive electrode material for sodium ion batteries of the present invention is a nickel-rich system, so that the number of redox active centers of the layered positive electrode material for sodium ion batteries is high during the charge and discharge process, thereby improving the discharge specific capacity of the layered positive electrode material for sodium ion batteries; Fe not only has a low cost, but also can smooth the charge and discharge curve; Co can reduce the electrochemical polarization of the layered positive electrode material for sodium ion batteries, and improve the rate performance of the layered positive electrode material for sodium ion batteries, while Mn and Ti, as inactive cations, do not participate in the electrochemical reaction, and play a role in supporting the main structure of the layered positive electrode material for sodium ion batteries, which can further improve the structural stability of the layered positive electrode material for sodium ion batteries.
[0034] Therefore, the sodium ion battery layered positive electrode material of the present invention has a high discharge specific capacity and excellent cycle stability, thereby being able to better promote the application of sodium ion batteries in low-speed electric vehicles.
[0035] Optionally, the sodium interlayer spacing of the sodium ion battery layered cathode material is Preferably Such a setting can better give play to the synergistic effect between calcium elements and sodium vacancies, and further improve the discharge capacity and cycle stability of the layered positive electrode material of the sodium ion battery.
[0036] Optionally, taking the sum of the molar numbers of Ni, Fe, Co, Mn and Ti in the sodium ion battery layered positive electrode material as 100, in any two regions of the same area of the sodium ion battery layered positive electrode material, the standard deviation of the Ni content is less than 0.2, the standard deviation of the Fe content is less than 0.3, the standard deviation of the Co content is less than 0.3, the standard deviation of the Mn content is less than 0.3, and the standard deviation of the Ti content is less than 0.1.
[0037] It can be understood that in the sodium ion battery layered positive electrode material of the present invention, the standard deviation of the content of Ni, Fe, Co, Mn, and Ti in any region of the same area of the sodium ion battery layered positive electrode material particles is small, that is, the standard deviation of the content in different regions of the sodium ion battery layered positive electrode material is small. Therefore, in the sodium ion battery layered positive electrode material of the present invention, Ni, Fe, Co, Mn, and Ti occupy transition metal sites and are evenly distributed, and there is no obvious segregation phenomenon, thereby being able to better improve the discharge specific capacity and cycle stability of the sodium ion battery layered positive electrode material.
[0038] It should be noted that the standard deviation of the content of each element Ni, Fe, Co, Mn, and Ti in any region of the same area in the present invention can be obtained by the following method: using SEM-EDS to test the content of each element in any two regions of the same area of the sodium ion battery layered positive electrode material particles, and using the standard deviation formula: Calculated, where n is the number of test areas, x i is the element content in the ith region, is the average value of the element content in each region.
[0039] Optionally, the particles of the sodium ion battery layered positive electrode material are plate-like particles, and the median particle size of the plate-like particles is 3 μm-5 μm. It should be noted that the median particle size of the plate-like particles in the present invention is actually the equivalent particle size of spherical particles, which is the equivalent result based on Mie theory after the powder particles are fully dispersed.
[0040] Optionally, the SPAN value of the sodium ion battery layered positive electrode material is 1.0-3.0. It should be noted that the SPAN value of the sodium ion battery layered positive electrode material in the present invention is (D 90 -D 10 ) / D 50 Calculated, where D 10 It refers to the particle size corresponding to the cumulative distribution of 10% in the material; D 50 It refers to the particle size corresponding to the cumulative distribution of 50% in the material; D 90 It refers to the particle size corresponding to when the cumulative distribution in the material accounts for 90%.
[0041] The present invention provides a method for preparing the layered positive electrode material for a sodium ion battery as described above, comprising the following steps:
[0042] S1, with [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O2 is used as a reference, wherein □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1, a sodium source, a calcium source, a nickel source, an iron source, a cobalt source, a manganese source and a titanium source are mixed to obtain a mixture, wherein the sodium source is in excess of 6%-10% based on the sodium element;
[0043] S2, sintering the mixture to obtain a sodium ion battery layered positive electrode material, wherein the sintering includes a first sintering and a second sintering, the first sintering temperature is 800°C-1000°C, the first sintering time is 12h-24h, the second sintering temperature is 600°C-900°C, and the second sintering time is 6h-12h.
[0044] In the preparation method of the sodium ion battery layered positive electrode material of the present invention, a high-temperature solid phase method is adopted to control the addition ratio of each raw material and limit the specific conditions of sintering, so as to obtain sodium vacancies and calcium elements with a specific ratio relationship in the sodium layer. The operation method is simple and easy to mass produce.
[0045] Taking into account that the sodium element in the sodium source will be partially lost during the subsequent sintering process, it can be understood that in step S1, by controlling the excess content of the sodium element in the sodium source, it is possible to supplement the amount of sodium element missing during the sintering process while ensuring that the sodium content in the layered positive electrode material of the sodium ion battery is greater than or equal to 0.9 and less than 1, that is, sodium vacancies are formed, and part of the sodium vacancies are occupied by calcium elements, thereby achieving the simultaneous introduction of sodium vacancies and calcium elements.
[0046] Optionally, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium nitrate, sodium oxalate and sodium sulfate.
[0047] Optionally, the calcium source is selected from at least one of calcium oxide, calcium hydroxide and calcium carbonate.
[0048] Optionally, the nickel source is selected from at least one of nickel oxide, nickel hydroxide and nickel carbonate, wherein the nickel carbonate is preferably basic nickel carbonate.
[0049] Optionally, the iron source is selected from at least one of ferrous oxide, ferrous oxide and ferrosoferric oxide.
[0050] Optionally, the manganese source is selected from trimanganese tetraoxide and / or manganese dioxide.
[0051] Optionally, the cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobalt carbonate and cobalt oxalate.
[0052] Optionally, the titanium source is selected from titanium dioxide and / or titanium nitrate.
[0053] It can be understood that in step S2, in the step of sintering the mixture, there is no specific limitation on the sintering environment, that is, there is no special limitation on whether it is in a specific atmosphere, as long as it can be sintered, that is, in an ordinary air atmosphere, it can also be sintered in an oxygen atmosphere. In the present invention, it is preferred to sinter the mixture in an air atmosphere. Such a setting is conducive to reducing production costs.
[0054] Optionally, the step of sintering the mixture specifically includes: firstly sintering the mixture, crushing, separating and screening to obtain an intermediate; and then sintering the intermediate, crushing, separating and screening. Such a setting is conducive to better controlling the particle uniformity, distribution uniformity of each element and structural stability of the layered positive electrode material of the sodium ion battery.
[0055] Furthermore, in the step of preparing the intermediate, after the first sintering is completed, it is cooled to room temperature and then crushed, separated and screened.
[0056] Similarly, after the second sintering is completed, the product is cooled to room temperature and then crushed, separated and screened.
[0057] Optionally, the median particle size of the intermediate is 3 μm-5 μm. This arrangement can better improve the uniformity of the distribution of each element in the sodium ion battery layered positive electrode material, and better control the particle uniformity and structural stability of the sodium ion battery layered positive electrode material.
[0058] In one embodiment, in the step of preparing the intermediate, a sieve is used for separation and screening.
[0059] In one embodiment, in the first sintering step, the heating rate is 1° C. / min-2° C. / min.
[0060] In one embodiment, the intermediate is subjected to a second sintering, and in the step of crushing, separation and screening, a sieve is used for separation and screening, so as to better control the particle uniformity of the sodium ion battery layered positive electrode material, that is, to better obtain particles of the sodium ion battery layered positive electrode material with a median particle size of 3μm-5μm.
[0061] In one embodiment, no matter after the first sintering or after the second sintering, before crushing, it is necessary to first cool down to room temperature before performing subsequent processing steps.
[0062] In addition, the present invention also provides a positive electrode sheet prepared using the sodium ion battery layered positive electrode material as described above.
[0063] And, a sodium ion battery prepared using the positive electrode sheet as described above. The sodium ion battery has a high discharge specific capacity and excellent cycle stability, thereby being able to better promote the application of sodium ion batteries in low-speed electric vehicles.
[0064] Hereinafter, the sodium ion battery layered positive electrode material and its preparation method and application will be further described by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0065] Example 1
[0066] According to [Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 in a stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and then the mixture is placed in a sagger, heated to 900°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 12 hours, cooled to room temperature, taken out, crushed and sieved to obtain an intermediate with a median particle size of about 3μm; the intermediate obtained above is placed in a sagger, kept warm at 600°C for 10 hours, taken out after cooling, crushed and sieved to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium layer spacing d O-Na-O for
[0067] from Figure 1 It can be seen that the sodium ion battery layered positive electrode material of this embodiment is in powder form, the microscopic morphology is plate-like particles, the median particle size is about 3.5 μm, and the SPAN value is 1.613.
[0068] In addition, the Avio200 inductively coupled plasma emission spectrometer was used to perform elemental testing on the sodium ion battery layered cathode material prepared in this embodiment. After testing, the molecular formula of the sodium ion battery layered cathode material in this embodiment conforms to [Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2.
[0069] Example 2
[0070] According to [Na 0.9 Ca0.04 □ 0.06 ][Ni 0.4 Fe 0.05 Co 0.05 Mn 0.4 Ti 0.1 ]O2 in a stoichiometric ratio, sodium sulfate, calcium oxide, nickel hydroxide, ferrous oxide, cobalt oxide, manganese oxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium sulfate has an excess of about 8% in terms of sodium element, that is, the actual molar amount of the Na element is 0.972, and then the mixture is placed in a sagger, heated to 800°C at a heating rate of 2°C / min in an air atmosphere, kept warm for 22 hours, cooled to room temperature, taken out, crushed and sieved to obtain an intermediate with a median particle size of about 4 μm; the intermediate obtained above is placed in a sagger, kept warm at 750°C for 8 hours, taken out after cooling, crushed and sieved to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.1 μm and the SPAN value is 1.344.
[0071] Example 3
[0072] According to [Na 0.98 Ca 0.01 □ 0.01 ][Ni 0.48 Fe 0.1 Co 0.05 Mn 0.32 Ti 0.05 ]O2 in a stoichiometric ratio, sodium hydroxide, calcium carbonate, nickel oxide, ferroferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium hydroxide has an excess of about 10% in terms of sodium element, that is, the actual molar amount of the Na element is 1.078, and then the mixture is placed in a sagger, heated to 1000°C at a heating rate of 3°C / min in an air atmosphere, kept warm for 12 hours, cooled to room temperature, taken out, crushed and sieved to obtain an intermediate with a median particle size of about 5 μm; the intermediate obtained above is placed in a sagger, kept warm at 900°C for 6 hours, taken out after cooling, crushed and sieved to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium layer spacing d O-Na-O for The median particle size is about 4.3 μm and the SPAN value is 2.405.
[0073] Example 4
[0074] Embodiment 4 is compared with embodiment 1, and the difference is only that according to [Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.44 Fe 0.13 Co0.03 Mn 0.35 Ti 0.05 ]O2[Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.44 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.7 μm and the SPAN value is 1.872.
[0075] Example 5
[0076] Embodiment 5 is compared with embodiment 1, and the difference is only that according to [Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.46 Fe 0.11 Co 0.03 Mn 0.35 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 4.0 μm and the SPAN value is 2.162.
[0077] Example 6
[0078] Example 6 is different from Example 1 in that, according to [Na 0.95 Ca 1 / 30 □ 1 / 60 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.5 μm and the SPAN value is 1.894.
[0079] Example 7
[0080] Example 7 is compared with Example 1, except that according to [Na 0.95 Ca 1 / 35 □ 3 / 140 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.4 μm and the SPAN value is 1.771.
[0081] Example 8
[0082] Embodiment 8 is compared with embodiment 1, and the difference is only that according to [Na 0.95 Ca 1 / 40 □ 1 / 40 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.4 μm and the SPAN value is 1.801.
[0083] Example 9
[0084] Example 9 is compared with Example 1, except that according to [Na0.95 Ca 1 / 60 □ 1 / 30 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.5 μm and the SPAN value is 1.834.
[0085] Example 10
[0086] Example 10 is different from Example 1 in that the size of the intermediate is 8 μm, and the other conditions are the same to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium interlayer spacing d O-Na-O for The median particle size is 8.0 μm and the SPAN value is 2.924.
[0087] Embodiment 11
[0088] Example 11 is different from Example 1 in that the mixture is placed in a sagger, heated to 900°C at a heating rate of 2°C / min in an air atmosphere, kept at this temperature for 12 hours, then cooled to 600°C and kept at this temperature for 10 hours, taken out after cooling, crushed and sieved to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium layer spacing d O-Na-O for The median particle size is about 5.2 μm and the SPAN value is 3.619.
[0089] The contents of Ni, Fe, Co, Mn and Ti in the six regions of the sodium ion battery layered positive electrode material of this embodiment were tested by scanning electron microscopy (SEM) + energy dispersive spectrometer (EDS), wherein the sum of the molar numbers of Ni, Fe, Co, Mn and Ti in the sodium ion battery layered positive electrode material is 100, the areas of the six regions are the same, and the six regions are respectively defined as region A, region B, region C, region D, region E, and region F, and the standard deviation of each element in any two regions is calculated, and the test results are shown in Table 1.
[0090] Table 1
[0091]
[0092] It can be seen from Table 1 that the distribution of Ni, Mn and Ti occupying transition metal sites in the layered cathode materials of sodium ion batteries is not uniform.
[0093] Example 12
[0094] Example 12 is different from Example 1 in that the mixture is placed in a sagger and heated to 900°C in an oxygen atmosphere at a heating rate of 2°C / min, and the other conditions are the same to obtain a layered positive electrode material for a sodium ion battery, wherein the sodium interlayer spacing d O-Na-O for The median particle size is about 3.4 μm and the SPAN value is 1.493.
[0095] Embodiment 13
[0096] Example 13 is compared with Example 1, except that according to [Na 0.95 Ca 0.03 □ 0.02 ][Ni 0.45 Fe 0.08 Co 0.03 Mn 0.41 Ti 0.03 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.8 μm and the SPAN value is 1.918.
[0097] The contents of Ni, Fe, Co, Mn and Ti in the six regions of the sodium ion battery layered positive electrode material of this embodiment were tested by scanning electron microscopy (SEM) + energy dispersive spectrometer (EDS), wherein the sum of the molar numbers of Ni, Fe, Co, Mn and Ti in the sodium ion battery layered positive electrode material is 100, the areas of the six regions are the same, and the six regions are respectively defined as region A, region B, region C, region D, region E, and region F, and the standard deviation of each element in any two regions is calculated, and the test results are shown in Table 2.
[0098] Table 2
[0099]
[0100] It can be seen from Table 2 that the standard deviation of the content of the same element in different regions is small, indicating that Ni, Fe, Co, Mn and Ti occupying the transition metal sites in the layered cathode material of sodium ion batteries are evenly distributed.
[0101] Comparative Example 1
[0102] Comparative Example 1 is compared with Example 1, except that 1.00 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.06, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.5 μm and the SPAN value is 1.708.
[0103] Comparative Example 2
[0104] Comparative Example 2 is compared with Example 1, except that 0.95 Ca 0.05 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.3 μm and the SPAN value is 1.818.
[0105] Comparative Example 3
[0106] Comparative Example 3 is compared with Example 1, except that 0.95 □ 0.05 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing dO-Na-O for The median particle size is about 3.5 μm and the SPAN value is 1.676.
[0107] Comparative Example 4
[0108] Comparative Example 4 is compared with Example 1, except that 0.95 Ca 1 / 80 □ 3 / 80 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.4 μm and the SPAN value is 1.718.
[0109] Comparative Example 5
[0110] Comparative Example 5 is compared with Example 1, except that 0.95 Ca 1 / 28 □ 1 / 70 ][Ni 0.42 Fe 0.13 Co 0.03 Mn 0.37 Ti 0.05 ]O2 stoichiometric ratio, sodium carbonate, calcium hydroxide, nickel carbonate, ferric oxide, cobalt oxide, manganese dioxide and titanium dioxide are fully mixed to obtain a mixture, wherein the sodium carbonate has an excess of about 6% in terms of sodium element, that is, the actual molar amount of the Na element is 1.007, and the other conditions are the same, to obtain a sodium ion battery layered positive electrode material, wherein the sodium layer spacing d O-Na-O for The median particle size is about 3.4 μm and the SPAN value is 1.508.
[0111] The XRD test of the sodium ion battery layered positive electrode materials of Examples 1 and 4-9 was performed using a Bruker D8AA25 X-ray diffractometer, wherein the target material used was a Cu target, the voltage was 40 kV, the current was 40 mA, and the test step was 0.015°. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the physical phases of the sodium ion battery layered positive electrode materials of Examples 1 and 4-9 all belong to the O3 phase.
[0112] At the same time, the XRD test of the sodium ion battery layered positive electrode materials of Example 1 and Comparative Examples 1 to 5 was performed using a Bruker D8AA25 X-ray diffractometer, and an enlarged view near the (003) peak was obtained from the corresponding XRD pattern, as shown in FIG. Figure 3 shown.
[0113] from Figure 3 It can be seen from the figure that after introducing some sodium vacancies on the basis of Comparative Example 1, the (003) peak of the sodium ion battery layered positive electrode material of Comparative Example 3 shifts to a low angle. According to the Bragg equation, the interlayer spacing of the sodium ion battery layered positive electrode material of Comparative Example 3 is enlarged. This is because after the sodium content is reduced, the shielding effect of the sodium layer on the adjacent oxygen is weakened. On the contrary, the sodium ion battery layered positive electrode material of Comparative Example 2 introduces some Ca vacancies into the sodium layer of Comparative Example 1. 2+ Afterwards, due to Ca 2+ With two positive charges, the interaction between adjacent oxygen is stronger, and the interlayer distance is reduced. 2+ , the two effects are balanced with each other, and the (003) peak is located between Comparative Example 2 and Comparative Example 3. Therefore, by simultaneously introducing sodium vacancies and calcium elements into the sodium layer and controlling the ratio between calcium elements and sodium vacancies, the sodium interlayer spacing in the layered positive electrode material of the sodium ion battery can be precisely regulated, and the sodium interlayer spacing can be controlled within a suitable range, and the synergistic effect between sodium vacancies and calcium elements can be fully utilized, and the sodium ion diffusion kinetics can be accelerated, so that more sodium ions can be reversibly deintercalated, and the discharge specific capacity can be increased, while the structural stability of the layered positive electrode material of the sodium ion battery is improved.
[0114] The sodium ion battery layered positive electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 to 5 were respectively prepared into corresponding half-cells. The specific preparation method is as follows: The sodium ion battery layered positive electrode materials of Examples 1 to 13 and Comparative Examples 1 to 5 were respectively dissolved in N-methylpyrrolidone (NMP) with a conductive agent (super-P) and a binder (PVDF) at a mass ratio of 90:5:5 to prepare a slurry. The prepared slurry was applied to the surface of the aluminum foil and dried. The loading amount of the sodium ion battery layered positive electrode material was 11 mg / cm 3 After cutting, the sodium sheet was used as the negative electrode in the glove box, 1M NaPF6 ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1:1) solution was used as the electrolyte, and 2032 button cells were used to assemble the half-cells. The cycle performance test of the half-cells obtained in Example 1 and Comparative Examples 1 to 5 was carried out. The test results are as follows: Figure 4As shown, the test method is as follows: after the battery is left for 30 minutes, it is charged to 4.2V at 0.1C, and after constant voltage is maintained at 0.05C, it is discharged to 1.5V at 0.1C.
[0115] from Figure 4 It can be seen that the capacity retention rates of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 are 94.1%, 75.1%, 85.1%, 74.2%, 78.1% and 82.3%, respectively.
[0116] The sodium ion battery layered positive electrode materials of Example 1 and Comparative Examples 1 to 5 obtained above were cycled 50 times under full battery conditions to test the charge-discharge cycle performance. Figure 5 It can be seen that compared with Comparative Examples 1-3, the sodium ion battery layered positive electrode material of this embodiment can give full play to the synergistic effect between the two elements due to the simultaneous introduction of sodium vacancies and calcium elements in the sodium layer and the control of the ratio between the two elements, so that the sodium ion battery layered positive electrode material has high discharge specific capacity and excellent cycle stability. At the same time, the half-cells of Comparative Examples 1 to 2 obtained above were charged and discharged for 10 cycles, and then XRD tests were performed using a Bruker D8A A25 X-ray diffractometer. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that after the cycle, compared with Comparative Example 1, since the sodium layer in Comparative Example 2 contains calcium, the degradation of the structure of the layered positive electrode material of the sodium ion battery can be inhibited, indicating that the introduction of calcium can improve the structural stability of the layered positive electrode material of the sodium ion battery after cycling.
[0117] The sodium ion battery layered positive electrode materials prepared in Examples 1 to 13 and Comparative Examples 1 to 5 are respectively prepared into corresponding full batteries, and the specific preparation methods are as follows: the preparation method of the full battery is different from the above-mentioned half-battery preparation method only in that after cutting, the full battery is assembled in a glove box with aluminum foil coated with hard carbon as the negative electrode.
[0118] The performance of the full battery obtained above was tested, and the test results are shown in Table 3, wherein the test method is as follows:
[0119] After the full battery obtained above was set aside for 1 hour, the cycle stability of the layered positive electrode material of the sodium ion battery was characterized using the Blue Electric Battery Test System. The test steps were as follows: 1 cycle of charge and discharge at 0.1C, 1 cycle of charge and discharge at 0.33C, and 48 cycles of 1C testing, where the capacity retention rate was defined as the ratio of the discharge capacity after the cycle to the discharge capacity of the first cycle of 1C.
[0120] Table 3
[0121]
[0122]
[0123] In addition, a relative trend chart is drawn for the discharge specific capacity and 50-cycle capacity retention rate of the sodium ion battery layered positive electrode materials of Example 1, Example 4 to Example 9 and Comparative Examples 1 to Comparative Examples 5. Figure 7 As shown, from Figure 7 It can be seen that based on Comparative Example 1, single doping with calcium or single introduction of sodium vacancies cannot take into account the improvement of the discharge specific capacity and capacity retention rate of the layered positive electrode material of the sodium ion battery. At the same time, there is a synergistic effect between calcium and sodium vacancies. The simultaneous introduction of calcium and sodium vacancies and controlling the amount and ratio of the two within a suitable range can accurately control the sodium interlayer spacing in the layered positive electrode material of the sodium ion battery, and the sodium interlayer spacing can be controlled within a suitable range. range, so that the sodium ion battery layered positive electrode material has a high discharge specific capacity and excellent cycle stability.
[0124] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0125] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A layered cathode material for a sodium ion battery, It is characterized in that The physical phase of the sodium ion battery layered positive electrode material is an O3 phase, and the molecular formula of the sodium ion battery layered positive electrode material is [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O 2 , where □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1.
2. The sodium ion battery layered positive electrode material according to claim 1, It is characterized in that The sodium interlayer spacing of the layered positive electrode material of the sodium ion battery is d O-Na-O , 3. The sodium ion battery layered positive electrode material according to claim 1, It is characterized in that Taking the sum of the molar numbers of Ni, Fe, Co, Mn and Ti in the sodium ion battery layered positive electrode material as 100, in any two regions of the same area of the sodium ion battery layered positive electrode material, the standard deviation of the Ni content is less than 0.2, the standard deviation of the Fe content is less than 0.3, the standard deviation of the Co content is less than 0.3, the standard deviation of the Mn content is less than 0.3, and the standard deviation of the Ti content is less than 0.
1.
4. The sodium ion battery layered positive electrode material according to claim 1, It is characterized in that The particles of the sodium ion battery layered positive electrode material are plate-like particles, and the median particle size of the plate-like particles is 3 μm-5 μm.
5. The sodium ion battery layered cathode material according to claim 1, It is characterized in that The SPAN value of the sodium ion battery layered positive electrode material is 1.0-3.
0.
6. A method for preparing the layered positive electrode material for sodium ion batteries according to any one of claims 1 to 5, It is characterized in that The following steps are involved: With [Na 1-x-y Ca x □ y ][Ni a Fe b Co c Mn d Ti e ]O 2 as a benchmark, wherein □ is a sodium vacancy, 0<x+y≤0.1 and 0.5≤y / x≤2, 0.4≤a<0.5, 0<b≤0.2, 0<c≤0.1, 0.3<d≤0.5, 0<e≤0.2, a+b+c+d+e=1, a sodium source, a calcium source, a nickel source, an iron source, a cobalt source, a manganese source and a titanium source are mixed to obtain a mixture, wherein the sodium source is in excess of 6%-10% based on the sodium element; The mixture is sintered to obtain a sodium ion battery layered positive electrode material, wherein the sintering includes a first sintering and a second sintering, the first sintering temperature is 800°C-1000°C, the first sintering time is 12h-24h, the second sintering temperature is 600°C-900°C, and the second sintering time is 6h-12h.
7. The method for preparing the layered positive electrode material for sodium ion batteries according to claim 6, It is characterized in that In the step of sintering the mixture, at least one of the following conditions is met: (1) placing the mixture in an air atmosphere for sintering; (2) The mixture is first subjected to a first sintering, and then crushed, separated and screened to obtain an intermediate; and then the intermediate is subjected to a second sintering, and then crushed, separated and screened.
8. The method for preparing the layered positive electrode material for sodium ion batteries according to claim 7, It is characterized in that The median particle size of the intermediate is 3 μm-5 μm.
9. A positive electrode sheet prepared using the sodium ion battery layered positive electrode material according to any one of claims 1 to 5.
10. A sodium ion battery prepared using the positive electrode sheet as claimed in claim 9.
Citation Information
Cited By
Doped sodium manganate positive electrode material and preparation method and application thereof
CN120413641A
Sodium ion positive electrode material and preparation method thereof
CN120978061A
A sodium-ion cathode material and its preparation method
CN120978061B
O3-phase layered oxide material and preparation method and application thereof
CN122314878A
